The Legal Capital Market Protection: Justice for Minority Stock Investors - Sudiyana Sudiyana; Foluke M Dare (Unissula, 2025)
The capital market is a critical component of a nation's economy, facilitating capital formation and allocation. Fraudulent practices, manipulation, lack of transparency, dishonesty and injustice in capital market activities must be dealt with firmly. This is because injustice can cause losses for minority stock investors. This study aims to analyze and evaluate the minority stock investor protection system in Indonesia, as well as efforts to improve justice and equality for all shareholders and examines the existing legal frameworks designed to protect minority stock investors and assesses their efficacy in ensuring justice. This study was a normative legal study, with a State approach, a Conceptual approach and a Case approach. The results of the study indicate that in the legal protection system according to Indonesian capital market law there are several findings that can result in injustice to Minority Investors. Building corporate governance that prioritizes and upholds the principle of honesty. Enforcement of the Transparency Principle in the implementation of capital market activities, both before listing, during listing, and after listing by changing the formulation of civil sanctions in the form of fines and compensation decided by the Financial Services Authority. As well as the involvement of minority investors in making important decisions in the issuing company.